IMF Staff papers : Volume 25 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1978)
This chapter examines if there was a fundamental shift in the demand for international reserves of countries in 1973 because of the change in the international monetary system from one of generally fixed exchange rates to one of greater exchange rate flexibility. Particular attention was also paid to the question whether the relationship between reserves and certain important variables remained stable during the period 1973-1976. The results indicated that there was a shift in the demand for reserves by industrial countries in response to the move to floating, however, that this shift occurred toward the end of 1973 rather than at the beginning of the year. Obviously, there was some lag in the response of these countries to the change in the system; however, the behavior of non-oil developing countries did not appear to be affected by the change. This can perhaps be attributed to the fact that most of these countries continued to peg their currencies to another currency, and thus there was no real change in the exchange rate regime relevant to them.